Total Flavone of Rhododendron Improves Cerebral Ischemia Injury by Activating Vascular TRPV4 to Induce Endothelium-Derived Hyperpolarizing Factor-Mediated Responses. (11th October 2018) - Han, Jun; Xu, Hang-Hang; Chen, Xiao-Long; Hu, Hao-Ran; Hu, Kun-Mei; Chen, Zhi-Wu; He, Guo-Wei
Abstract : Background . Total flavonoids of Rhododendron (TFR) is extracted from Rhododendron, a herbal medicine widely used in China. The main components are flavone compounds such as warfarin, rutin, quercetin, and hyperoside. We investigated the role of TRPV4 channel in the TFR induced endothelium-dependent hyperpolarizing factor- (EDHF-) mediated responses against ischemia/reperfusion injury (IR) in cerebral IR (CIR) rats. Methods . The morphological changes of cerebral cortex, the relaxation of cerebral basal artery (CBA), and cell membrane potential recording were studied in CIR rats. The outward potassium current in smooth muscle cell was recorded by whole-cell patch clamp recording. The protein expression of TRPV4, SKca, and IKca was determined. Confocal laser was used to measure the Ca 2+ fluorescence intensity. Results . After treatment with TFR, the number of pyramidal cells in brain tissue increased and the number of empty or lightly stained cells decreased and these effects were eliminated by using HC-067047, Apamin, or TRAM-34. TFR induced and EDHF-mediated dilatation and hyperpolarization in CBA were also attenuated by using these inhibitors. The increased outward current density elicited by TFR in acutely isolated CBA smooth muscle cells was abolished by using TRAM-34 and Apamin. TFR upregulated the protein expression of TRPV4, SKca, and IKca that was also eliminated by these inhibitors. Laser scanning showed that the increased mean fluorescence intensity of Ca 2+ by CIR was decreased by using TFR and that this effect was again eliminated by the above inhibitors. Conclusions . We conclude that in the CBA of the CIR rats the protective effect of TFR on ischemic cerebrovascular injury may be related to the activation of the TRPV4 in both endothelium and smooth muscle by increasing its expression and activity. The activation of TRPV4 channel in the endothelium may be linked to the opening of endothelial IKca/SKca channels that induces EDHF-mediated relaxation and hyperpolarization in the smooth muscle cell. In addition, the activation of TRPV4 in the smooth muscle cell in CBA may be linked with the activation of BK C a channel through a TRPV4-dependent pathway, reduce Ca 2+ concentration in the cell, and relaxes the vessel. These findings may form a new therapeutic target for protection of ischemic brain injury and facilitate the use of Chinese medicine in brain protection.